THE EFFECT OF THE IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL AS A STRATEGY TO IMPROVE HIGHER-ORDER THINKING SKILLS OF STUDENTS IN CLASS XI SOCIAL ON ECONOMIC LEARNING AT EAST JAKARTA SENIOR HIGH SCHOOL - Sucy Fhatma Delima; Siti Nurjanah; Aditya Pratama (Yayasan Education and Social Center, 2023)
This study aims to improve the Higher-Order Thinking Skills of students using the Discovery Learning model at the high school level in economic learning. The method used in this study is Quasi-experimental with Non-Equivalent Control Group Design. The population of this study is all students of SMA Negeri 50 Jakarta and SMA Negeri 59 Jakarta. Samples of this study were students of Class XI Social 1 and XI Social 2 at SMA Negeri 59 Jakarta and Class XI Social 1 and XI Social 4 at SMA Negeri 50 Jakarta school, where Class XI Social 1 at SMA Negeri 59 and SMA Negeri 50 Jakarta used as a control class using conventional learning models and Class XI IPS 2 and XI IPS 4 at SMA Negeri 59 and SMA Negeri 50 Jakarta as experimental classes using Discovery Learning models. The research instruments used were pretest and posttest of Higher-Order Thinking Skills. The results showed that the data were normally distributed and homogeneous. The results of parametric statistical analysis is done by the technique of data analysis One-Tailed T Test (Right Side) with Independent Sample T-Test. For the value of N-Gain score data is normally distributed and homogeneous, then the One-Tailed T Test (Right Side) with an Independent Sample T-Test N-Gain. The results showed that (1) Higher-Order Thinking Skills of learners between classes that use the Discovery Learning model (experimental class) is higher than Higher-Order Thinking Skills of learners who use the conventional learning model (control class). This is evidenced by the results of hypothesis testing with One-Tailed T Test (Right Side) > value is 4.265 > 1.656 and Sig. (1-tailed) of 0.000. Because 0.000 < 0.05 so it can be stated that H₀ is rejected and Hₐ is accepted. (2) The improvement of Higher-Order Thinking Skills of learners between classes that use the Discovery Learning model (experimental class) is higher than the Higher-Order Thinking Skills of learners who use the conventional learning model (control class). This is evidenced by the results of hypothesis testing with a One-Tailed T Test (Right Side) obtained by Sig. (1-tailed) amounted to 0.0125. Because 0.0125 < 0.05 so it can be stated that H₀ is rejected and Hₐ is accepted.